The Effect of Different Sulphur Sources Applied at Various Rates on Soil pH - Fatma Nur Kılıç; Osman Sönmez (Turkish Journal of Agriculture: Food Science and Technology)
Soil pH, governed by the relative concentrations of hydrogen () and hydroxyl () ions, is a key factor affecting the chemical, physical, and biological properties of soils. Most soils in Türkiye are alkaline due to calcareous parent material and climatic influences, which restricts the availability of essential nutrients to plants. Sulphur applications are widely employed to reduce soil pH and increase nutrient bioavailability. The use of Sulphur for the amelioration of alkaline soils will continue to be a crucial strategy for enhancing agricultural sustainability in the future. This study investigates the effects of different Sulphur sources on the pH of sandy and clay-loam texture soils. This study investigates the effects of different Sulphur sources on the pH of sandy and clay loam textured soils. The soil samples used in the research were taken from Pınarbaşı and Melikgazi districts of Kayseri province, and soil samples were taken from both regions from a depth of 30 cm and from 20 randomly determined different points. Sulphur applications were applied at rates of (0, 0.02, 0.04 g 100 g-1) (X: powdered Sulphur ) and (0, 0.044, 0.088 g 100 g-1) (Y: granular Sulphur ) based on weight for clay-loam and sandy textured soils, respectively. Samples taken on days 0, 15, 30, 60, 90, 180, and 360 post-applications showed that the impact of Sulphur applications on soil pH change was significant across all treatments (p<0.01). The lowest pH measurement, 6.92, was observed in sandy textured soils with an application from granular Sulphur at 0.088 g 100 g-1. The pH change in clay-loam textured soils was found to range from 8.13 to 7.79, and in sandy textured soils from 7.69 to 6.92. These changes suggest that the acidifying effect of Sulphur oxidation on soil pH varies depending on the soil’s buffering capacity, particle size ratio, application rate, and incubation day. Consequently, the granular Sulphur was found to be more effective compared to the control and powdered Sulphur , and an application rate of 0.088 g 100 g-1 might be effective for both clay-loam and sandy soils. However, due to its lack of economic feasibility, 0.044 g dose or the doses from powdered Sulphur might be more appropriate.